Implementation of Good Governance Principles in the Land Transportation Management Center - Karunia, R. Luki; Solihati, Keisha Dinya; Wati, Nila Kurnia (KnE Social Sciences, 2022)
To achieve globalization and modernization, public organizations must implement good governance in order to respond to and meet community expectations. One of these expectations is land transportation management, which in Indonesia is handled by the Land Transportation Management Center (BPTD). Good governance should be implemented in BPTD in the hopes of improving performance and, as a result, community satisfaction, and resolving problems with ground transportation. BPTD still has a number of issues to deal with, including the state of the transportation infrastructure for road, urban, river and lake transportation and crossings, transportation safety, and administrative issues. This study examined how four principles of good governance have been implemented at BPTD: accountability, transparency, openness, and the rule of law. The study focused on BPTD Region IX in West Java Province, BPTD Region IX in Central Java Province, and DIY provinces. This study employed qualitative descriptive methods. According to the findings, BPTD has implemented the principles of good governance, but it still has room for improvement by sharpening its performance indicator targets, making LAKIP more widely known, measuring community satisfaction, and pursuing independent innovation. Keywords: transportation, good governance, accountability, transparency